Safe Tractor Operations: Foundations of Tractor Safety: AE599, 6/2024 - Gorucu, Serap; Lehtola, Carol J.; Brown, Charles M. (EDIS, 2024)
The Safe Tractor Operations series contains six articles devoted to tractor safety. This publication aims to familiarize new and beginning farmers, Extension agents and specialists, and the public with safe tractor operations. It gives guidance about how everyone in an agricultural operation can work together to make using tractors safer. Written by Serap Gorucu, Carol J. Lehtola, and Charles M. Brown and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2024.